1969
DOI: 10.1002/ajpa.1330310114
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of isoniazid acetylase enzyme deficiency among Egyptians

Abstract: The frequency of isoniazid slow inactivators is very high among Eqyptians, 82% have more than 0.91 y/ml of free INH in serum specimens obtained six hours after a single dose of 10 mgm/kgm. The incidence of the allele for INH acetylase enzyme deficiency is estimated at 0.9059 and that of the heterozygous carrier of this allele at 0.1705.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2
2

Year Published

1972
1972
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 3 publications
0
11
2
2
Order By: Relevance
“…A study from Scan dinavia shows urban Denmark and rural Sweden to have 61 and 51% slow pheno types, respectively; results which do not vary statistically from those presented here [Lower et al, 1979], whilst American groups are similar [Harris, 1963], and Jews have somewhat more of the slow pheno type. The Japanese, Chinese, and Eskimos populations have been shown to have the fewest members with the slow phenotypes [Armstrong and Peart, 1960;Harris, 1963;Evans, 1963], The only other results for a Middle Eastern population deals with a series of 50 Egyptians [Hashem et al, 1969] which showed 82% slow inactivation -results statistically different from those reported here for the Iraqi population (p<0.01). This, in part, may be due to the quite dif ferent technique used by these authors who measured isoniazid and acetylisoniazid in plasma and urine samples from their subjects.…”
Section: Discussioncontrasting
confidence: 62%
“…A study from Scan dinavia shows urban Denmark and rural Sweden to have 61 and 51% slow pheno types, respectively; results which do not vary statistically from those presented here [Lower et al, 1979], whilst American groups are similar [Harris, 1963], and Jews have somewhat more of the slow pheno type. The Japanese, Chinese, and Eskimos populations have been shown to have the fewest members with the slow phenotypes [Armstrong and Peart, 1960;Harris, 1963;Evans, 1963], The only other results for a Middle Eastern population deals with a series of 50 Egyptians [Hashem et al, 1969] which showed 82% slow inactivation -results statistically different from those reported here for the Iraqi population (p<0.01). This, in part, may be due to the quite dif ferent technique used by these authors who measured isoniazid and acetylisoniazid in plasma and urine samples from their subjects.…”
Section: Discussioncontrasting
confidence: 62%
“…The frequencies of acetylator pheno types in various ethnic groups have been investigated and found to range from nearly 100% rapid acetylators in the Cana dian Eskimos [Jeaneset al, 1972] to about 18% in Egyptians [Hashem et al, 1969]. Most populations of oriental origin show a much higher frequency of rapid acetylators than other populations [for review see Lunde et al, 1977].…”
Section: Introductionmentioning
confidence: 99%
“…De même, au Zimbabwe, Nhachi et al ont aussi trouvé une répartition bimodale avec 58 % d'acétyleurs lents et 42 % d'acétyleurs rapides [58]. Dans une population égyptienne, la fréquence d'acétyleurs lents est supérieure à 90 % [59]. Par contre, chez les Esquimaux, près de 99 % des sujets sont des acétyleurs rapides.…”
Section: Discussionunclassified
“…Selon Muscat, la NAT2 est une voie importante de toxification des contaminants comme le 4-aminobiphényl qui forme des adduits à l'hémoglobine chez les fumeurs et la survenue de cancer de la vessie serait plus importante chez les sujets fumeurs acétyleurs lents. Les résultats des autres pays africains montrent aussi une prévalence d'acétyleurs rapides plus importante au Zimbabwe et en Tanzanie [59,64].…”
Section: Discussionunclassified